Bi-PE: bi-directional priming improves CRISPR/Cas9 prime editing in mammalian cells. Issue 11 (10th June 2022) - Tao, Rui; Wang, Yanhong; Jiao, Yaoge; Hu, Yun; Li, Li; Jiang, Lurong; Zhou, Lifang; Qu, Junyan; Chen, Qiang; Yao, Shaohua
Abstract: Prime editors consisting of Cas9-nickase and reverse transcriptase enable targeted precise editing of small DNA pieces, including all 12 kinds of base substitutions, insertions and deletions, while without requiring double-strand breaks or donor templates. Current optimized prime editing strategy (PE3) uses two guide RNAs to guide the performance of prime editor. One guide RNA carrying both spacer and templating sequences (pegRNA) guides prime editor to produce ssDNA break and subsequent extension, and the other one produces a nick in the complementary strand. Here, we demonstrated that positioning the nick sgRNA nearby the templating sequences of the pegRNA facilitated targeted large fragment deletion and that engineering both guide RNAs to be pegRNAs to achieve bi-direction prime editing (Bi-PE) further increase the efficiency by up to 16 times and improved the accuracy of editing products by 60 times. In addition, we showed that Bi-PE strategy also increased the efficiency of simultaneous conversion of multiple bases but not single base conversion over PE3. In conclusion, Bi-PE strategy expanded the editing scope and improved the efficiency and the accuracy of prime editing system, which might have a wide range of potential applications.